الاتجاهات الاساتذة التعليم الابتدائي نحو دور التعليم التحضيري في تحسين التحصيل الدراسي - عدة, كريمة (كلية العلوم الاجتماعية, 2019)
هدفت هذه الد ا رسة إلى التعرف عمى طبيعة اتجاهات الأساتذة التعميم الابتدائي نحو دور التعميم التحضيري في تحسين التحصيل الد ا رسي ، ولتحقيق الأهداف الد ا رسة استخدمت الباحثة المنهج الوصفي، واختيرت عينة من الأساتذة التعميم الابتدائي بالمدرستي بمبشير حمو والمدرسة موساوي ميمود تابعة لمقاطعة 1 بولاية مستغانم 2018 / 2019 ، حيث تكونت من) 27 ( أستاذا تم تصميم من طرف الطالبة، وأما الأدوات الد ا رسة فتمثمت الاستبيان لقياس الاتجاهات اتجاهات التعميم الابتدائي نحو دور التعميم التحضيري في تحسين التحصيل الد ا رسي ، يتكون من ) 35 ( فقرة ، وقد اعتمدت الباحثة عمى برنامج الحزمة الإحصائية spss20 وأساليب إحصائية المعتمدة عميها التك ا ر ا رت والنسب المؤوية واختبار) مان وتني يو( وكانت النتائج كالتالي: - لأساتذة التعميم الابتدائي الاتجاهات الايجابية نحو دور التعميم التحضيري في تحسين التحصيل الد ا رسي. - لا يوجد فروو ذات دالة الإحصائية في الاتجاهات للأساتذة التعميم الابتدائي نحو دور التعميم التحضيري في تحسين التحصيل الد ا رسي تعزى في متغير الجنس. -لا يوجد فروو ذات دالة الإحصائية في الاتجاهات للأساتذة التعميم الابتدائي نحو دور التعميم التحضيري في تحسين التحصيل الد ا رسي تعزى في متغير المستوى التعميمي. - لا يوجد فروو ذات دالة الإحصائية في الاتجاهات للأساتذة التعميم الابتدائي نحو دور التعميم التحضيري في تحسين التحصيل الد ا رسي تعزى في متغير خبرة المهنية The aim of this study was to identify the nature of the attitudes of primary education teachers toward the role of preparatory education in improving scholastic achievement . To achieve the objectives of the study, the researcher used the descriptive approach. A sample of teachers was selected for primary education at the schools of Belbechir Hamou and Musawi Meloud of district 1 in Mostaganem State 2018/2019. Where it consisted of (27) professors designed by the student. The study tools consisted of a questionnaire to measure trends in primary education trends towards the role of preparatory education in improving scholastic achievement. Consists of (35) paragraph, the researcher has adopted the statistical package program spss20 And statistical methods based on repetitions and percentages and the test (Man and Tiny Yu) The results were as follows: -Primary education teachers have positive attitudes towards the role of preparatory education in improving scholastic achievement. - There are no statistically significant differences in attitudes of primary school teachers toward the role of preparatory education in improving scholastic achievement attributable to the sex variable. - There are no statistically significant differences in the attitudes of primary school teachers towards the role of preparatory education in improving scholastic achievement attributable to the variable education level. - There are no statistically significant differences in attitudes of primary education teachers toward the role of preparatory education in improving scholastic achievement attributable to the variable professional experience.
دراسة ميدانية عينة التعليم الابتدائي في ولاية مستغانم
Keywords: التعليم التحضيري؛الاستاذ التعليم الابتدائي؛الاتجاهات؛التحصيل الدراسي